PENGEMBANGAN BAHAN AJAR CETAK BERBASIS PENILAIAN KINERJA SEBAGAI SUMBER BELAJAR BAGI SISWA SD KELAS VI - Ermaniatu N; M. Taufik (PGSD Universitas Negeri Medan, 2017)
This study aims to identify the characteristics of the print instructional materials sufficient to increase the ability of science students to be able to apply the concept of science in everyday life. Limited scale test conducted on 10 students of class VI SDN Tembong 2. Data were obtained using a questionnaire method using printed teaching materials based performance assessment. Data processing questionnaire using Likert scale. The conclusion in this study is the result of the analysis of testing experts that the performance assessment based teaching material can be a source of learning and show good results with their respective test scores for the acquisition of 80.95% scientists, education experts test 96%, 85.33% expert test design and test a limited scale at 93.5%.Keywords: Print Instructional Materials, Performance Assessment.